Gender Equity and Leadership, from Rhetoric to Reality in Ghana: Finding the Way - Ampofo, Annie Afua (UniMAC-GIJ, 2020)
This paper is a review of recent literature on issues of gender within the context of leadership. The ebbs and flow of democratic process in the world has brought the urgent need for countries to ensure gender equality/equity in all aspects of our lives including leadership. Based on this, several protocols, frameworks and policies take into consideration issues of gender balance to ensure women are given equal participation in leadership roles. For example, the African Union Agenda 2063 aspiration 6 requires that African countries development agenda provides the need for people-centered development and gender equality, which places the African people at the center of all continental efforts, to ensure their participation in the transformation of the continent, and to build caring and inclusive societies. It recognizes that no society can reach its full potential, unless it empowers women and remove all obstacles to women‘s full participation in all areas of human endeavors; and unless it provides an enabling environment for its children and young people to flourish and reach their full potential (African Union Commission, 2014). Agenda 2063 document identifies widespread gender inequalities between men and women in disproportionate manner where women carry the heavy burden of poverty, diseases and illiteracy. The framework anticipate that by the year 2063, Africa will be a continent where the critical role of women in Africa‘s transformation is recognized and they are proactively harnessed.
MA Journalism